In Vivo Functional Assessment of Sodium-Glucose Cotransporters (SGLTs) Using [18F]Me4FDG PET in Rats. (21st June 2022) - Matsusaka, Yohji; Chen, Xinyu; Arias-Loza, Paula; Werner, Rudolf A.; Nose, Naoko; Sasaki, Takanori; Rowe, Steven P.; Pomper, Martin G.; Lapa, Constantin; Higuchi, Takahiro
Abstract : Background . Mediating glucose absorption in the small intestine and renal clearance, sodium glucose cotransporters (SGLTs) have emerged as an attractive therapeutic target in diabetic patients. A substantial fraction of patients, however, only achieve inadequate glycemic control. Thus, we aimed to assess the potential of the SGLT-targeting PET radiotracer alpha-methyl-4-deoxy-4-[ 18 F]fluoro-D-glucopyranoside ([ 18 F]Me4FDG) as a noninvasive intestinal and renal biomarker of SGLT-mediated glucose transport. Methods . We investigated healthy rats using a dedicated small animal PET system. Dynamic imaging was conducted after administration of the reference radiotracer 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG), or the SGLT-targeting agent, [ 18 F]Me4FDG either directly into the digestive tract (for assessing intestinal absorption) or via the tail vein (for evaluating kidney excretion). To confirm the specificity of [ 18 F]Me4FDG and responsiveness to treatment, a subset of animals was also pretreated with the SGLT inhibitor phlorizin. In this regard, an intraintestinal route of administration was used to assess tracer absorption in the digestive tract, while for renal assessment, phlorizin was injected intravenously (IV). Results . Serving as reference, intestinal administration of [ 18 F]FDG led to slow absorption with retention of 89.2 ± 3.5 % of administered radioactivity at 15 min. [ 18 F]Me4FDG, however, was rapidly absorbed into the blood and cleared from the intestine within 15 min, leading to markedly lower tracer retention of 18.5 ± 1.2 % (P < 0.0001 ). Intraintestinal phlorizin led to marked increase of [ 18 F]Me4FDG uptake (15 min, 99.9 ± 4.7 %; P < 0.0001 vs. untreated controls), supporting the notion that this PET agent can measure adequate SGLT inhibition in the digestive tract. In the kidneys, radiotracer was also sensitive to SGLT inhibition. After IV injection, [ 18 F]Me4FDG reabsorption in the renal cortex was significantly suppressed by phlorizin when compared to untreated animals (%ID/g at 60 min, 0.42 ± 0.10 vs. untreated controls, 1.20 ± 0.03 ; P < 0.0001 ). Conclusion . As a noninvasive read-out of the concurrent SGLT expression in both the digestive tract and the renal cortex, [ 18 F]Me4FDG PET may serve as a surrogate marker for treatment response to SGLT inhibition. As such, [ 18 F]Me4FDG may enable improvement in glycemic control in diabetes by PET-based monitoring strategies.